Pengaruh Daya Tarik Wisata Dan Promosi Terhadap Jumlah Kunjungan Wisatawan Di Pantai Panrita Lopi Kecamatan Muara Badak - Fahmi Ahmadin (Jurnal Administrasi Bisnis Fisipol Unmul, 2022)
This study aims to determine whether or not the influence of the factors of interest in visiting, namely tourist attraction and promotion on the number of tourist visits to Panrita Lopi Beach, Kec. Kutai Kartanegara Rhino Estuary. The subjects in this study were tourists who visited Panrita Lopi Beach, Kec. Muara Badak, with the number of samples used as many as 100 respondents and with an age limit above the age of 18 years - 50 years who can be respondents in this study. The results of this study indicate if there is an influence between Tourist Attraction and Promotion with the Number of Tourist Visits at Panrita Beach Lopi Kec. Muara Badak, Kutai Kartanegara Regency with a standardized regression value of (0.256). The results of the t test show t count (2.168) with a significance value of 0.01 using a confidence level of = 95% (0.05). Then other results found that there is no influence between promotion and interest in visiting is explained by the coefficient value of the promotion variable from the standardized regression equation of (0.082). The results of the t test show t count (0.843) with a significance value of 0.40. By using = 95% (0.05). Then the results of all the variables when tested together get results. Based on the F test, the calculated F is 3.909 with a significance level of 0.02. Because the probability is much smaller than 0.05 (0.02 <0.05) and F count is greater than F table (3.909 > 3.09) which means that there is a significant influence between attractiveness and promotion on the number of tourist visits, with the results of the coefficient showing a number of 0.560 which can be interpreted if the tourist attraction and promotion variable contributes 56% to the number of tourist visits at Panrita Beach Lopi Kec. Muara Badak, Kutai Kartanegara Regency and the remaining 44% of the contribution was given by variables or other factors outside of this research.